Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Bappeda Kabupaten Tangerang - Al Fiqi; Armaniah, Henny (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Employee performance in government institutions such as BAPPEDA of Tangerang Regency is crucial to ensuring the success of regional development planning. However, based on the 2024 Key Performance Indicator (KPI) data, most performance indicators have not met the 90% target, including attendance rates, document digitization, and responsiveness to incoming letters, which averaged below 75%. Pre-survey results also revealed weaknesses in organizational culture implementation, such as a lack of innovation space and leadership openness, as well as low job satisfaction, especially regarding work atmosphere and compensation. This research employs a quantitative approach using a survey method with a Likert-scale questionnaire. The population and sample consist of 52 employees, and data analysis techniques include validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The t-test results show that organizational culture (t = 2.297; sig. = 0.026) and job satisfaction (t = 2.639; sig. = 0.011) have a positive and significant effect on employee performance. The F-test produced an F value of 6.439 > 3.187 with sig. = 0.003, indicating that both variables simultaneously have a significant effect. The coefficient of determination (R²) of 64.7% demonstrates that organizational culture and job satisfaction can explain variations in employee performance, while the remaining 35.3% is influenced by other factors.